Genomics and Pharmacogenomics in Anticancer Drug Development and Clinical Response - Innocenti, Federico (Cancer Drug Discovery and Development, 2009)
The availability of new molecular approaches to the selection of drug therapy is an emerging need, as the traditional approach based on the evaluation of patient and tumor characteristics is clearly far from optimal. Many, and in most cases the majority of treated patients do not have significant benefits from the treatment while they often experience moderate to severe toxicities. In "Pharmacogenomics, Anticancer Drug Discovery, and Response," edited by Federico Innocenti, readers will find a series of chapters addressing the role of genomic information in cancer therapy and in drug development representing a unique source, as it describes experimental approaches, statistical strategies, and clinical examples of the application of genomic medicine in oncology. This book provides the most comprehensive body of knowledge on the role of genetic and genomic variation in the individualization of drug therapies in cancer patients.